Ecological criteria for designing effective MPA networks for large migratory pelagics: Assessing the consistency between IUCN best practices and scholarly literature. (May 2021) - Allan, Jamie C.; Beazley, Karen F.; Metaxas, Anna
Abstract: Networks of Marine Protected Areas (MPAs) have been proposed as one tool for the protection of large, migratory pelagic species, but debate exists on the utility of MPAs for these species. International conservation arenas have developed criteria for effective MPA networks, with the IUCN-WCPA [1] outlining five ecological guidelines in designing resilient MPA networks. This review examines recent literature to: (1) assess the degree to which the five IUCN guidelines address large migratory at-risk pelagic species; (2) assess differences between the scientific literature and IUCN guidelines in the manner in which effective MPA networks are conceptualized for these species; (3) identify additional relevant design themes for effective conservation of migratory pelagics through MPA networks not addressed by the IUCN guidelines; and, (4) identify challenges and opportunities for the design of MPA networks for this suite of species. Results indicate that neither the literature nor the IUCN-WCPA guidelines provide comprehensive strategies for designing MPA networks for large, migratory pelagic species. The study concludes that the IUCN-WCPA guidelines can be potentially effective for these species if migratory connectivity is fully accounted for and complementary adaptive and dynamic mechanisms are developed for integration across wider seascapes and sectors at large regional and global scales. To this end, updates to the design guidelines for MPA networks are warranted, particularly with respect to connectivity, adaptive and dynamic approaches, and international collaborations. Greater clarity and consistency in the definitions and uses of the terms MPAs and MPA networks is warranted to facilitate collaborative efforts. Highlights: Studies generally reflect IUCN guidelines but give less frequent attention to spacing, shape, and migration routes. IUCN guidelines could better protect migratory species by acknowledging the importance of fidelity behaviours. IUCN guidelines can be potentially effective if connectivity and complementary adaptive and dynamic mechanisms are developed. Updates to IUCN guidelines are warranted for connectivity, adaptive and dynamic approaches, and international collaborations. Greater clarity and consistency in definitions and usage of key terms in marine conservation is warranted.